2017
DOI: 10.1177/1029864917700706
|View full text |Cite
|
Sign up to set email alerts
|

Adopting a music-to-heart rate alignment strategy to measure the impact of music and its tempo on human heart rate

Abstract: Music is frequently used as a means of relaxation. Conversely, it is used as a means of arousal in sports and exercise contexts. Previous research suggests that tempo is one of the most significant determinants of music-related arousal and relaxation effects. Here we investigate the specific effect of music tempo, but also more generally, the influence of music on human heart rate. We took the pulses of 32 participants in silence, and then we played them non-vocal, ambient music at a tempo corresponding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 44 publications
1
32
1
1
Order By: Relevance
“…As mentioned before, the durations of the SloMo videos of our study were also underestimated, indicating that there could be cross-modal effects of stretched time both for visual and auditory stimuli. In another recent study, the tempo of the music was both accelerated and decelerated [ 52 ]. While the slower tempi in the digitally stretched music condition led to decreases in mean heart rate, no effects were found for versions in higher tempi.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, the durations of the SloMo videos of our study were also underestimated, indicating that there could be cross-modal effects of stretched time both for visual and auditory stimuli. In another recent study, the tempo of the music was both accelerated and decelerated [ 52 ]. While the slower tempi in the digitally stretched music condition led to decreases in mean heart rate, no effects were found for versions in higher tempi.…”
Section: Discussionmentioning
confidence: 99%
“…Both the rhythms of cardiac activity and of musical behaviors form long time series of interrelated events; a few studies have addressed how heart rate modulations and musical tempo change together over time. For example, passive listening to music has shown decreased heart rate in response to slower-tempo music (Van Dyck et al, 2017) and increased heart rate during fast-tempo music (Gomez and Danuser, 2007). Heart rate variability during music listening changes less predictably; da Silva et al (2014) found no difference in HRV between rest (baseline) and music listening, whereas Bretherton et al (2019) reported that only some tempo manipulations elicited HRV changes relative to a rest condition.…”
Section: Cardiac Activity During Music Behaviorsmentioning
confidence: 99%
“…This result is in contrast to positive manipulations of the HR in both tempo directions as reported in previous studies (Bason & Celler, 1972; Fukumoto & Nomura, 2009; Saperston, 1993). These ambiguous results may be explained by the fact that Van Dyck et al (2017) did not match the physiological preconditions for entrainment. As reported by Bason and Celler (1972) and Saperston (1993), successful manipulation of the HR only occurred when the frequency of the stimulus was coupled to the actual HR of a listener in real-time and when the stimulus was presented within a critical time window (‘within approximately one beat of the heart rate’, Saperston, 1993, p. 1).…”
mentioning
confidence: 97%
“…Concerning the entrainment effect, a recent study of Van Dyck et al (2017) found effects on the HR using discontinuous and random changes in musical tempo only for substantial tempo decreases. In their study, non-vocal ambient music was presented to 32 participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation